A Fuzzy Analysis Approach to Part Family Formation in Cellular Manufacturing Systems - Dhanalakshmi, V; Arunachalam, S; SANKARANARAYANASAMY, K; Page, T (Studies in Informatics and Control, 2008)
Part family formation using fuzzy cluster analysis in Group Technology (GT) and feature recognition for tool access direction using relationship matrix in Computer Aided Process Planning (CAPP) have been presented in this paper. In the process of identifying part-families and machine groups, Fuzzy Cluster Analysis to form machine-part fuzzy relative matrix which converted into a zero-one conventional matrix. A new similarity coefficient, which involves all the entries of the machine-part fuzzy relative matrix resulting in a more realistic part family formation was suggested. The feature extraction system presented in this paper is designed to extract features from a STEP file in Boundary Representation (B-Rep) and Attributed Adjacency matrix. The system is able to automatically extract alternate tool axis directions (TADs). There is a potential applications in set-up change cost optimisation and fixture selection.